2019
DOI: 10.1002/ajhb.23270
|View full text |Cite
|
Sign up to set email alerts
|

Social mobility of the father influences child growth: A three‐generation study

Abstract: Objectives: The association between body height and social status is known. We were interested in the effect of intergeneration changes in social status on height. Methods: Body height was measured in 2008 paternal grandfather-father-son and 1803 paternal grandfather-father-daughter triplets. The sample consisted of four child cohorts born in 1988, 1985, 1983, and 1980, and was measured annually from 6 to 11, 9 to 14, 11 to 16, and 14 to 18 years of age. Triplets were dichotomized according to grandfathers' oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…As a result, distribution of heights within a community clusters around the mean (Aßmann & Hermanussen 2013). Similar phenomena are reported by a study on Polish children (Koziel & Gomula 2017;Koziel et al 2019). This is to say the tall height communities generate tall people and short height communities generate short people.…”
Section: Discussionsupporting
confidence: 84%
“…As a result, distribution of heights within a community clusters around the mean (Aßmann & Hermanussen 2013). Similar phenomena are reported by a study on Polish children (Koziel & Gomula 2017;Koziel et al 2019). This is to say the tall height communities generate tall people and short height communities generate short people.…”
Section: Discussionsupporting
confidence: 84%
“…Basnet et al linked maternal resources for care to child growth and found a strong association between maternal education and child outcomes, influencing height and mental well-being (Basnet et al 2019). Similar results were found by Scheffler et al (2018) and Koziel et al (2019), who revealed significant positive effects of higher parental education on growth results in their analysis of height in children from India. This association between higher levels of maternal education and increased growth could even be observed across different socio-cultural contexts (Lakshman et al 2013).…”
Section: Parental Educationmentioning
confidence: 71%
“…They also observed a strong effect of intra-and intergenerational social mobility on growth outcomes. Low-class fathers who have attained higher education raised taller sons than low-class fathers who stayed in a low class or even than upper-class fathers who lost their social advantage (Koziel et al 2019). Furthermore, the act of migrating between social classes seemed to affect growth of socially mobile individuals as well and not only growth among their offspring.…”
Section: Social Mobilitymentioning
confidence: 97%
See 1 more Smart Citation
“…It has explicitly been mentioned since more than 100 years that upper class children grow taller than lower class children, and that they grow taller irrespective of their nutrition (Hermanussen, Bogin, & Scheffler, ; Schlesinger, ). Koziel, Zaręba, Bielicki, Scheffler, and Hermanussen () studied the effect of intergeneration changes in social status on height in a three‐generation setting and showed that upward social mobility results in taller and downward social mobility, in shorter stature within the same family.…”
mentioning
confidence: 99%